Public health education to change the global health conversation - Galea, Sandro (Salud pública de México, 2022)
Population health is driven by the forces in the world around us. Those forces, in turn, are determined by a national and global conversation about priorities and values.This highlights the challenges public health faces to achieve its broader aspirations. The long-drawn national and global debates about what to prioritize and how collective resources should be invested are influenced, both positively and negatively, by a wide variety of factors. Political considerations about where resources should be deployed and who benefits from them and who does not, are a central part of any national or global conversation. Similarly, commercial stakeholders have a particular and legitimate interest in a broader conversational environment, given the impact this topic can have on their commercial viability. Additionally, broader public conversations depend on the millions of small-scale conversations at the proverbial kitchen table that, together, lead to change and form the national and global consensus. This essay establishes the need to catalize, on small and large scales, the underpinnings of public health on an ongoing basis.